2005
DOI: 10.1021/cm050083o
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive, Regioregular Alkoxy-Functionalized Polythiophenes:  A New Class of Stable, Low Band Gap Materials

Abstract: Presented here is the synthesis and unique physical properties for a new class of highly processable regioregular poly(3-alkoxy-functionalized thiophenes). These polymers exhibit high electrical conductivities with very good stabilities (over 3 years) when doped with iodine vapor followed by exposure to ambient conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 44 publications
4
87
0
Order By: Relevance
“…were also synthesized [45][46][47][48][49][50]. Although no detailed study on the polymerization mechanism was reported, the polymerization may also follow chain-growth mechanism.…”
Section: Pt4-pt9mentioning
confidence: 99%
“…were also synthesized [45][46][47][48][49][50]. Although no detailed study on the polymerization mechanism was reported, the polymerization may also follow chain-growth mechanism.…”
Section: Pt4-pt9mentioning
confidence: 99%
“…The on/off current ratio were quite low reaching values of 50. This is related to the relatively high off-current (I ds at V g = 0 V) probably originated by the low oxidation potential and highly stable p-type conductive state of alkoxy-substituted conjugated systems [30]. LS POPT OTFTs fabricated on bare t-SiO 2 substrates exhibit much worse field-effect properties.…”
Section: Field-effect Propertiesmentioning
confidence: 99%
“…[6] As a consequence, the Grignard metathese method (GRIM), starting from the dibromothiophene derivative -as is used for the chain-growth polymerization of HT-P3AT -cannot be employed for the polymerization of HT-P3AOT, since this methods produces both isomers. [10] Also a selective GRIM on 2-iodo-5-bromo-3-alkoxythiophene, even if iPrMgCl·LiCl was employed, was unsuccessful in our hands.…”
Section: Molar Mass Versus [M] 0 /[In]mentioning
confidence: 82%